Evaluation of One- and Two-Step Impression Techniques and Vertical Marginal Misfit in Fixed Prothesis - Sina Radfar; Marzieh Alikhasi; Sotude Khorshidi; Saba Tohidkhah; Reza Morvaridi Farimani; Sima Shahabi (International Journal of Dentistry)
Objectives/Purposes. This study compared one-step and two-step impression techniques. Methods. 12 impressions were made of a resin maxillary model (second premolar and second molar) with two prepared abutment teeth using vinyl polysiloxane (VPS); the margin of the second premolar was 0.5 mm subgingivally; and the margin of the second molar tooth was at the level of the gingiva. Impressions were made using two techniques: one-step and two-step putty/light materials. A three-unit metal framework was fabricated on the master model using the computer-aided design/computer-aided manufacturing (CAD/CAM) technique. The vertical marginal misfit was evaluated in the buccal, lingual, and mesial and distal surfaces of the abutments on the gypsum casts using a light microscope. Data were analyzed using the independent t-test (α < 0.05). Results. The results showed significantly lower vertical marginal misfit in all six areas evaluated around the two abutments in the two-step impression technique compared with the corresponding values in the one-step technique. Conclusion. Vertical marginal misfit in the two-step technique with a preliminary putty impression was significantly lower than in the one-step putty/light-body technique.